Robust Observer-based Trajectory Tracking Control for Unmanned Aerial Manipulator - Liang, Jiacheng; Chen, Yanjie; Lai, Ningbin; He, Bingwei (International journal of control, automation, and systems, 2023)
This paper aims at the stable motion control problem of the unmanned aerial manipulator (UAM) with internal interactions and external environment disturbances, and proposes a robust observer-based trajectory tracking control framework. Considering the large-dimensional nonlinearity and underactuated of UAM dynamics, a separate control scheme is adopted, including a geometric controller for quadrotor UAV and prescribed performance control (PPC) method for onboard active manipulator (OAM). In particular, an observer-based geometric control scheme is developed for the position and attitude tracking of the quadrotor UAV to ensure steady flight, where the quadrotor UAV attitude is represented by the rotation matrix to eliminate singularities or ambiguities. Subsequently, an observer-based PPC method is presented for the OAM to guarantee the prescribed transient and steady-state performance responses. Finally, the simulation comparisons and experimental study validate the effectiveness and performances of the proposed control framework.